Fighting the Pes Plague, Tegal 1927-1935: Living in the Midst of a Health Crisis - Faradziba, Shifa Aulya; Wijayati, Putri Agus (Universitas Islam Negeri Sumatera Utara, 2025)
This study examines the plague outbreak that struck the Tegal region between 1927 and 1935, focusing on its transmission routes, the response of the colonial government, and the participation of the local community. Employing historical methods comprising heuristics, verification, interpretation, and historiography this research presents a historical narrative that identifies ports and railway lines as primary factors in the spread of the disease. Unsanitary environmental conditions and the limited number of healthcare personnel further accelerated the outbreak. The colonial government's policies indicate that significant progress in managing the epidemic was achieved after 1934, marked by improved healthcare services and vaccination efforts. This study affirms that the successful containment of the outbreak depended on the integration of public health policies, active community involvement, and adequate infrastructure readiness. This study aims to identify the routes and causes of the spread of the plague in Tegal, as well as the mitigation efforts carried out by the Government at that time. Furthermore, this research is important as a reference for educating healthcare professionals and the general public today about plague outbreaks caused by rat fleas.